Effects of working capital management on firm performance: Evidence from the EFQM certified firms - Muhammad Yousaf; Petr Bris (Cogent Economics & Finance, 2021)
The main aim of the current study is to explore the relationship between working capital (WC) and firm performance. We chose a sample of 326 Czech firms, including 20 certified firms from the EFQM (European Foundation for Quality Management) Excellence Model from the Albertina database. The sample of the Czech firms was taken from three sectors: manufacturing, automobile, and construction. We employed a two-step system generalized method of moment (GMM) technique to determine the results. The study results revealed a negative impact of WC on firm performance; moreover, the firms having a quality certificate from the EFQM Excellence Model perform better. The findings of previous research, which were held globally, and the current study results will encourage the directors, managers, and leaders of the Czech firms to participate in the quality award.
Keywords: 330; Albertina; Czech firms; dummy variable; EFQM Model; GMM